Effects Of Camptothecin On Pichia Pastoris Strain Smd1168h Expressing Dna Topoisomerase I On Agar Plates - Devi Vadiveloo, Sajetra (Pusat Pengajian Teknologi Industri, 2020)
DNA topoisomerase I (TopoI) is a ubiquitous enzyme, that is responsible for releasing topological stress by introducing a temporary nick in one strand of the DNA helix and later, resealing the single-stranded DNA. TopoI is involved in cell proliferation; therefore, overexpression of this enzyme in a cell often mimics cancer cells. Hence, this enzyme plays a major role in molecular biology studies for developing various types of antineoplastic agents, such as camptothecin. Camptothecin exhibits strong anti-inhibitory properties towards the catalytic activity of TopoI by preventing the re-ligation of the nicked DNA, resulting in shear stress and eventually, cell death. Pichia pastoris expression system is well-known for its ability to produce human-like endogenous TopoI compared to other expression systems, e.g. Escherichia coli, Saccharomyces cerevisiae and baculovirus. Currently, searching for more effective compounds to reduce the toxicity of cancer treatments, while still producing similar effects as current chemotherapy regimens is required. As such, this research aims to investigate the inhibitory properties of camptothecin on the growth of recombinant clones of multi-copy number insert of P. pastoris transformants expressing human DNA topoisomerase I (SMD1168H-pPICZαA-hTopoI) grown on yeast extract agar and microbiological agar plates, respectively. The agar plates contained different concentrations of camptothecin (25 µM, 50 µM, 75 µM and 100 µM) and were left to incubate for 3 days. In conclusion, the highest inhibitory activity of camptothecin was observed when both the recombinant clones were grown in microbiological agar plate that contained 100 µM of camptothecin.